Drives and tasks in bank marketing - Onyiriuba, Leo (NFS Bureau Limited, 2013)
This implies that bank marketing transcends the picture of it portrayed by those bankers. Unfortunately, while the erroneous views persist, there are skills gaps in customer service and managing banking relationships. The irony of this situation is that marketing provides structure for, and nourishes, these important functions. In fact, customer service and relationship management are the major building blocks of bank marketing. In writing this book, the author demonstrate the practical issues, lessons, and solutions with which bankers and customers must contend, with suggestions on how to meet their mutual expectations and needs.